Invasive Carcinoma Ex-Pleomorphic Adenoma of the Lacrimal Gland with a Cystadenocarcinoma Component: A Case Report and Review of the Literature - Vamsee K. Neerukonda; Bryant Carruth; Maria Del Valle Estopinal (Case Reports in Pathology)
Lacrimal gland neoplasms comprise up to 18% of all orbital masses clinically and histologically. Much of our current core knowledge regarding lacrimal gland tumors stems from prior study of their more common counterparts, the salivary glands. The prognosis for each lacrimal gland tumor is contingent upon proper clinical evaluation and ultimately the histopathologic diagnosis. We describe a case of an invasive carcinoma ex-pleomorphic adenoma (Ca-ex-PA) with a cystadenocarcinoma component arising from the lacrimal gland in the absence of any previously diagnosed pleomorphic adenoma (benign mixed tumor) or prior incisional surgery. This case illustrates the importance of the histopathologic assessment including immunohistochemistry and genetic testing to narrow a differential diagnosis and potentially aid or guide therapy in the future. Our finding suggests that carcinoma of the lacrimal gland may be derived from previously undiagnosed and perhaps even subclinical pleomorphic adenoma.